Superficial stellate cells of the dorsal cochlear nucleus - Apostolides, Pierre F.; Trussell, Laurence O. (Frontiers in Neural Circuits, 2014)
The dorsal cochlear nucleus (DCN) integrates auditory and multisensory signals at the earliest levels of auditory processing. Proposed roles for this region include sound localization in the vertical plane, head orientation to sounds of interest, and suppression of sensitivity to expected sounds. Auditory and non-auditory information streams to the DCN are refined by a remarkably complex array of inhibitory and excitatory interneurons, and the role of each cell type is gaining increasing attention. One inhibitory neuron that has been poorly appreciated to date is the superficial stellate cell. Here we review previous studies and describe new results that reveal the surprisingly rich interactions that this tiny interneuron has with its neighbors, interactions which enable it to respond to both multisensory and auditory afferents.